2016
DOI: 10.1016/j.tele.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Gratifications of digital photo sharing on Facebook

Abstract: Despite the rapid adoption of Facebook as a means of photo sharing, minimal research has been conducted to understand user gratification behind this activity. In order to address this gap, the current study examines users' gratifications in sharing photos on Facebook by applying Uses and Gratification (U&G) theory. An online survey completed by 368 respondents identified six different gratifications, namely, affection, attention seeking, disclosure, habit, information sharing, and social influence, behind shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
229
3
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(293 citation statements)
references
References 51 publications
14
229
3
20
Order By: Relevance
“…These results were expected based on the findings of Baek et al (2014), Ko et al (2005), Luo et al (2011), Malik et al (2016, Pentina et al (2014). They demonstrated that the success of Second Life in the e-learning processes depends on a combination of convenience, sharing experience and the search for more entertaining educational programmes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 54%
See 2 more Smart Citations
“…These results were expected based on the findings of Baek et al (2014), Ko et al (2005), Luo et al (2011), Malik et al (2016, Pentina et al (2014). They demonstrated that the success of Second Life in the e-learning processes depends on a combination of convenience, sharing experience and the search for more entertaining educational programmes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 54%
“…According to Malik, Dhir and Nieminen (2016) entertainment refers to relaxation, fun and enjoyment whilst engaging in an activity or with people. For Ha et al (2015) entertainment is a hedonic gratification.…”
Section: Uses and Gratifications Theory And Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than looking at what it is that media does to people it looks at the functions that the media provides for people, considering the motivations of an audience as critical. Considered one of the most effective frameworks, scholars have used U&G theory to explore a variety of social media sharing behaviour, including sharing links (Baek et al 2011), news (Hanson and Haridakis 2008;Lee and Ma 2012) and photos (Malik et al 2016;Sung et al 2016). Given that social psychology theories focus on relationship establishment and group behaviour, as well as the extensive application of U&G theory in examining the variety of motivations in social media, it was decided that U&G was an acceptable theoretical foundation for the study.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Literature on sharing behaviour has identified entertainment as a strong motivation (e.g. Baek et al 2011;Holton et al 2014;Malik et al 2016;Sung et al 2016;Taylor et al 2012), with U&G studies also finding that it is one of the most dominant gratifications (e.g. Lee and Ma 2012;Park et al 2009).…”
Section: Entertainmentmentioning
confidence: 99%